Response of fertilizer application on yield and economics of papaya (Carica papaya) (Current Horticulture, 2024)
The experiment was conducted to find out the response of fertilizer application on yield and yield attributes of papaya (Carica papaya L.) var. Red Lady" during 2016-17 at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari (Gujarat). The experiment was laid out with nine treatments in a randomized block Design (RBD) and replicated thrice. The treatments included 100% RDF (200:200:250 g NPK/plant) as the control in four equal splits (2, 4, 6 and 8 MAP), 100 and 80% recommended dose of nitrogen and potash in 8 equal splits starting from 2nd month after planting at 30 days interval with or without foliar application of 1% Grade-IV micronutrient and novel organic liquid fertilizer at 2, 4, 6 and 8 month after planting. Results revealed that papaya var. Red Lady plants fed with 80% RDNK (160:200 g/ plant) and applied in 8 equal splits starting from 2 month after planting at 30 days interval with foliar application of novel organic liquid fertilizer at 2, 4, 6 and 8 month after planting gave maximum number of fruits per plant, average fruit weight (kg), diameter of fruit (cm), length of fruit (cm), yield (kg/plant and t/ha), maximum net realization and benefit : cost ratio.
Keywords: Foliar application; Grade-IV micronutrient; Novel organic liquid fertilizer; Red Lady; Split application